Learn more about

Refine search

Results (displaying all 38 matches)

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
676.b.17576.1 676.b \(y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1\) $E_1$ 0
713.b.713.1 713.b \(y^2 + (x^3 + x + 1)y = -x^4\) $\mathrm{USp}(4)$ 0
745.a.745.1 745.a \(y^2 + (x^3 + x + 1)y = -x\) $\mathrm{USp}(4)$ 0
862.b.862.1 862.b \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - x - 1\) $\mathrm{USp}(4)$ 0
1042.a.1042.1 1042.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 + 2x + 2\) $\mathrm{USp}(4)$ 0
1696.b.434176.1 1696.b \(y^2 + xy = x^6 - 2x^5 + 2x^4 + 9x^3 - 12x^2 + 3x + 26\) $N(G_{3,3})$ 0
2230.a.8920.1 2230.a \(y^2 + xy = x^5 + x^4 - x^3 + 2x^2 - 3x + 1\) $\mathrm{USp}(4)$ 0
2404.a.4808.1 2404.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 + x\) $\mathrm{USp}(4)$ 0
2673.a.8019.1 2673.a \(y^2 + (x^3 + x + 1)y = -2x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
2768.a.354304.1 2768.a \(y^2 + y = x^6 - 4x^4 - 5x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2810.a.89920.1 2810.a \(y^2 + xy = -x^6 - 3x^5 + 5x^3 - 3x + 1\) $\mathrm{USp}(4)$ 0
2916.a.5832.1 2916.a \(y^2 + (x^3 + 1)y = x^3\) $J(E_1)$ 0
2916.b.11664.1 2916.b \(y^2 + y = x^6\) $D_{3,2}$ 0
3274.a.13096.1 3274.a \(y^2 + xy = x^5 - 4x^3 + 3x + 1\) $\mathrm{USp}(4)$ 0
3428.a.6856.1 3428.a \(y^2 + (x^3 + 1)y = x^4 + x^2 - x\) $\mathrm{USp}(4)$ 0
3568.d.913408.1 3568.d \(y^2 + x^3y = x^4 - 5x^3 + 5x^2 - 2x + 1\) $\mathrm{USp}(4)$ 1
4132.a.66112.1 4132.a \(y^2 + (x^3 + 1)y = x^3 - 2x^2 + 2x - 2\) $\mathrm{USp}(4)$ 0
4752.d.608256.1 4752.d \(y^2 + x^3y = x^5 + 5x^4 + 11x^3 + 26x^2 + 28x + 33\) $\mathrm{USp}(4)$ 0
4900.a.98000.1 4900.a \(y^2 + y = x^6 + 4x^4 + 4x^2 + 1\) $G_{3,3}$ 0
7012.a.112192.1 7012.a \(y^2 + (x^3 + 1)y = 2x^4 + 4x^2 - 2x\) $\mathrm{USp}(4)$ 0
7562.a.241984.1 7562.a \(y^2 + (x^2 + 1)y = x^6 - 3x^5 + 2x^4 - x^3 - x^2 + 3x + 1\) $\mathrm{USp}(4)$ 0
10260.b.164160.1 10260.b \(y^2 + (x^3 + 1)y = -2x^4 + 6x^2 - 4\) $\mathrm{USp}(4)$ 1
10449.a.31347.1 10449.a \(y^2 + (x^3 + x + 1)y = x^4 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 0
11536.a.369152.1 11536.a \(y^2 + (x + 1)y = x^6 - x^4 + x^3\) $\mathrm{USp}(4)$ 0
11728.d.187648.1 11728.d \(y^2 + (x^3 + x)y = x^3 - x + 1\) $\mathrm{USp}(4)$ 0
11792.b.377344.1 11792.b \(y^2 + (x + 1)y = x^6 + x^4 - x^3\) $\mathrm{USp}(4)$ 0
17689.d.866761.1 17689.d \(y^2 + (x^3 + x^2 + 1)y = 2x^4 - 2x^2 - 7x + 5\) $G_{3,3}$ 2
23012.a.368192.1 23012.a \(y^2 + (x^2 + x + 1)y = 4x^5 + 8x^4 + x^2 + x\) $\mathrm{USp}(4)$ 0
26244.c.157464.1 26244.c \(y^2 + (x^3 + 1)y = 2x^3\) $J(E_1)$ 0
26244.d.314928.1 26244.d \(y^2 + y = x^6 - 2x^3\) $J(E_3)$ 1
26244.e.472392.1 26244.e \(y^2 + (x^3 + 1)y = 2\) $J(E_3)$ 0
31775.a.158875.1 31775.a \(y^2 + (x^3 + x + 1)y = -3x^4 + 6x^2 + 2x\) $\mathrm{USp}(4)$ 0
50220.a.803520.1 50220.a \(y^2 + (x^3 + 1)y = -x^5 - x^4 + x^3 + 7x^2 + 16x + 10\) $\mathrm{USp}(4)$ 0
52488.a.629856.1 52488.a \(y^2 + (x^3 + x)y = x^4 - 7x^2 + 6\) $G_{3,3}$ 1
68225.a.341125.1 68225.a \(y^2 + (x^3 + x + 1)y = 2x^4 + 6x^2 - 3x\) $\mathrm{USp}(4)$ 0
98172.a.589032.1 98172.a \(y^2 + (x^3 + 1)y = -3x^4 + 9x^2 + 3x\) $\mathrm{USp}(4)$ 0
150660.a.903960.1 150660.a \(y^2 + (x^3 + 1)y = 3x^4 + 9x^2 - 3x\) $\mathrm{USp}(4)$ 0
163782.b.491346.1 163782.b \(y^2 + (x^2 + 1)y = -2x^6 + 17x^4 - 9x^3 - 26x^2 - 6x + 32\) $\mathrm{USp}(4)$ 0


Download all search results for